Predictors for Anterior Cruciate Ligament (ACL) Re-injury after Successful Primary ACL Reconstruction (ACLR) - Gupta, R (Malays Orthop J, 2020)
INTRODUCTION: Few authors have addressed risk factors related to an ipsilateral graft rupture and contralateral anterior cruciate ligament (ACL) injury after return to sports (RTS) following primary ACL reconstruction. MATERIAL AND METHODS: Patients with ACL re-injury to either knee after successful primary ACLR were included in Group I and those with no further re-injury were included in Group II. Variables including age, gender, side, body mass index (BMI), thigh atrophy, anterior knee laxity difference between both knees measured by KT-1000 arthrometer, mean time of return to sports (RTS), graft type, type of game, mode of injury, Tegner Activity Score, hormone levels, femoral tunnel length (FTL), posterior tibial slope (PTS) and notch width index (NWI) were studied. Binary logistic regression was used to measure the relative association. RESULTS: A total of 128 athletes were included with 64 in each group. Mean age in Group I and II were 24.90 and 26.47 years respectively. Mean follow-up of Group I and Group II were 24.5 and 20.11 months respectively. Significant correlation was present between ACL re-injury and following risk factors; PTS of >10º, KT difference of >3.0mm, thigh atrophy of >2.50cm and time to RTS <9.50 months P value <0.05). No correlation was found with age, sex, BMI, type of game, Tegner Activity Score, mode of injury, NWI, size of graft, FTL and hormone levels. CONCLUSION: Possible risk factors include PTS of ≥ 10º, KT difference of ≥ 3.0mm at 1 year follow-up, thigh atrophy of ≥ 2.50cm at 1 year follow-up and RTS <9.5 months after primary ACLR.